2019
DOI: 10.1016/j.jpedsurg.2019.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Current operative management of congenital lobar emphysema in children: A report from the Midwest Pediatric Surgery Consortium

Abstract: The purpose of this study was to evaluate the clinical presentation and operative outcomes of patients with congenital lobar emphysema (CLE) within a large multicenter research consortium. Methods: After central reliance IRB-approval, a retrospective cohort study was performed on all operatively managed lung malformations at eleven participating children's hospitals (2009-2015). Results: Fifty-three (10.5%) children with pathology-confirmed CLE were identified among 506 lung malformations. A lung mass was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 42 publications
5
27
0
1
Order By: Relevance
“…For the total disease percentage we found a cut-off at 18% for cystic abnormalities (sensitivity 31%, specificity 98%, and accuracy 86%) and 17% for CLO (sensitivity 66%, specificity 89%, and accuracy 86%). Our study cohort was comparable to that in previous studies in terms of distribution of CLA diagnoses, [23][24][25] disease extent, 26,27 development of symptoms, and reason for surgical resection. In our cohort, nearly two-thirds of patients remained asymptomatic, which proportion is comparable to that in previous studies ranging from 55% to 74%.…”
Section: Cut-offsupporting
confidence: 79%
See 1 more Smart Citation
“…For the total disease percentage we found a cut-off at 18% for cystic abnormalities (sensitivity 31%, specificity 98%, and accuracy 86%) and 17% for CLO (sensitivity 66%, specificity 89%, and accuracy 86%). Our study cohort was comparable to that in previous studies in terms of distribution of CLA diagnoses, [23][24][25] disease extent, 26,27 development of symptoms, and reason for surgical resection. In our cohort, nearly two-thirds of patients remained asymptomatic, which proportion is comparable to that in previous studies ranging from 55% to 74%.…”
Section: Cut-offsupporting
confidence: 79%
“…35 On the contrary, lesions may also appear larger on CT due to hyperinflation. 24 Identification of specific CT-features may be of value in predicting outcome for prospective studies. To this end, we assessed individual components of the CLAQ method and found that hyperdensity within lesions were associated with an increased probability of becoming symptomatic and having a lower exercise tolerance.…”
Section: Outcome Predictionmentioning
confidence: 99%
“…The progressive air trapping became more clinically apparent by 4 weeks of age with diagnostic radiological findings that were missed at the time. This insidious onset of symptoms of respiratory distress symptoms is in keeping with CLE 8. Patients with CLE normally present with respiratory distress in infancy, hyperinflated chest, compression of healthy lung tissue, cyanosis and bronchial hypoplasia 10…”
Section: Discussionsupporting
confidence: 54%
“…The diagnosis is usually supported by a chest X-ray demonstrating hyperlucency, ipsilateral atelectasis, mediastinal shift, widened rib space and diaphragmatic flattening 11. It most often occurs in the upper and middle lobes with the left upper lobe having the highest incidence as in this case, with rates reported of 45% and 57% 8 12…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation